THE INFLUENCE OF SCHOOL CLIMATE & RELIGIOSITY ON THE SCHOOL WELL BEING OF STUDENTS AT SMPN 1 PUNGGING - Roofidah, Rizka Choirur; Ansyah, Eko Hardi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the influence of school climate and religiosity on the school well-being of students at SMPN 1 Pungging. Method: Employing a quantitative approach with a multiple linear regression design, data were collected from 209 students selected through simple random sampling. Results: The analysis revealed that school climate significantly and positively influences school well-being (β = 0.619; p < 0.001), whereas religiosity shows a positive but statistically insignificant effect (β = -0.026; p = 0.472). The coefficient of determination (R² = 0.367) indicates that school climate and religiosity jointly explain 36.7% of the variance in school well-being, with the remaining 63.3% attributed to other factors. Novelty: The study offers empirical evidence that, in the context of Indonesian public schools, a positive school climate plays a more critical role than religiosity in shaping students’ school well-being. This highlights the importance of fostering a supportive, inclusive, and engaging school environment as a strategic focus for enhancing student welfare.